Modulation of pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation by ursolic acid (UA) attenuates rifampin-isoniazid cytotoxicity - Chang, Hsiao-Yun; Chen, Chao-Jung; Ma, Wei-Chih; Cheng, Wai-Kok; Lin, Yen-Ning; Lee, Ying-Ray; Chen, Jih-Jung; Lim, Yun-Ping (Phytomedicine (Stuttgart), 2017)
Interactions between transcriptional inducers of cytochrome P450 (CYP450) enzymes and therapeutic drugs may be prevented by antagonizing the activation of a nuclear receptor (NR), pregnane X receptor (PXR, NR1I2), thus improving therapeutic efficacy. In the present study, we aim to identify that ursolic acid (UA), a widely distributed pentacyclic triterpene, may act as an effective antagonist of PXR and its sister NR receptor, constitutive androstane receptor (CAR, NR1I3). The hepatocellular carcinoma cell line, HepG2, was used to evaluate the promoter activity of PXR and CAR target genes, CYP3A4 and CYP2B6, respectively. Catalytic activities, mRNA, and protein expression of CYP3A4 and CYP2B6 were evaluated in a differentiated HepaRG cell line. Coregulation of PXR with coregulators on CYP3A4 promoter response elements was also been characterized. Transient transfection assays showed that UA effectively attenuated CYP3A4 and CYP2B6 promoter activities mediated by rifampin (RIF, human PXR agonist) and CITCO (human CAR agonist). These inhibitory effects were well correlated with the expression and catalytic activities of CYP3A4 and CYP2B6. Furthermore, the interaction of co-regulators with PXR and the transcriptional complexes in the CYP3A4 promoter activity and CYP3A4 promoter xenobiotic response element (everted repeat 6, ER6), respectively, were disrupted in the presence of UA. UA showed an antagonistic effect against PXR, and reversed the cytotoxic effects of isoniazid (INH) induced by RIF. Taken together, these results show that UA inhibits the transactivation effects of PXR and CAR, and reduces the expression and function of CYP3A4 and CYP2B6. The present study suggests that UA could be a powerful agent for reducing potentially dangerous interactions between transcriptional inducers of CYP enzymes and therapeutic drugs. [Display omitted]